Rituximab and Pirfenidone in the Treatment of Steroid‐Refractory Bleomycin Lung Injury - Aasir M. Suliman (14150217) (2025)
Bleomycin‐induced lung injury (BILI) is a well‐recognised but potentially life‐threatening complication of ABVD chemotherapy (adriamycin, bleomycin, vinblastine and dacarbazine), often requiring prompt diagnosis and intervention. We present a case of a 43‐year‐old female with Hodgkin's lymphoma who developed progressive respiratory symptoms following her fourth cycle of ABVD. A broad infectious and autoimmune workup was unremarkable, and chest imaging was consistent with interstitial lung disease. Her condition deteriorated despite empirical antibiotics and high‐dose corticosteroids. The addition of rituximab and pirfenidone led to significant clinical and radiological improvement, highlighting the potential role of these agents in managing steroid‐refractory BILI. Other Information Published in: Respirology Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/rcr2.70228